(untitled) (Analele Universității București.Geografie, 2024)
Maximum daily precipitations play a crucial role in the occurrence of flood risk, particularly when combined with other natural and human factors, such as the geographical and morphological characteristics of the area, as seen in the case of Tebessa city. The city is situated below surrounding mountains, with the Wadi El Kebir valley passing through it to the north. This study aims to simulate the risk of flooding in Tebessa city. The approach involves utilizing GIS programs for DEM (Digital Elevation Model) analysis, extracting the study area, obtaining morphometric parameters and maps, and employing the Turraza, Sokolovsky, and Maillet-Gouthier equations to calculate the frequency of maximum daily flows for return periods of 10, 50, 100, and 200 years. Based on this, the flood volume is calculated. Finally, the HEC-RAS program is used to simulate flood risk in the Wadi El Kebir valley, and urban vulnerability maps are generated for Tebessa city for each return period.